MEDIAL AND LATERAL POSTERIOR TIBIAL SLOPE IN THE SKELETALLY IMMATURE: A HUMAN CADAVERIC STUDY. Issue 3 (31st March 2019) - Anchustegui, Nicolas G.; Rustad, Audrey; Shea, Cooper; Troyer, Stockton; Dingel, Aleksei; Ganley, Theodore J.; Shea, Kevin; Milbrandt, Todd A.
Background: Recent research has identified posterior tibial slope as a risk factor for anterior cruciate ligament (ACL) injury, due to increased forces on the ACL with this tibial anatomy. Biomechanical studies suggest that altering a patient's posterior tibial slope may lower the risk of ACL injury. Due to the presence of an open physis, guided growth may be used to reduce the posterior tibia slope in this high risk skeletally immature population. The primary purpose of this study was to quantify and measure the posterior tibial slope in pediatric knees. Methods: Forty-four pediatric knee CT scans were analyzed using OsiriX, an imaging software. Specimens analyzed were between the ages of 2 and 12 years of age. The proximal tibial slope for each specimen was measured on CT scan sagittal slices at 2 locations: 1) At the medial tibial plateau at the mid region of the medial femoral condyle, as determined on a coronal slice through the femoral condyle; 2) At the lateral tibial plateau at the mid region of the lateral femoral condyle, as determined on the coronal slice through the femoral condyle. The measurement of the posterior tibial slope was determined by placing two lines parallel to the diaphysis of the tibia, one located in the middle of the diaphysis and one located at the most posterior aspect of the diaphysis. The most proximal aspect of both the medial and lateral tibial plateau were then identified and angle measurements were taken in reference to the parallel lines. The angle measurements were plotted graphically by age in order to account for variability in development within age groups. The anterior medial and lateral tibia plateau widths were measured by identifying the mid region of the respective plateaus. From this point, the distance between the top of the tibial plate and the physis was measured. Results: The average posterior tibial slope angle for the medial and lateral tibial plateau were (5.53° ± 4.17°) and (5.95° ± 3.96°) respectively. Independent samples t-test and ANOVA indicate the difference between the posterior tibial slope angle of the medial and lateral tibial plateau were not statistically significant (p < 0.05). When plotted graphically by age, a slight negative trend between age and posterior tibial slope was identified. As age increases, the medial and lateral posterior tibial slope decreases. The mean anterior medial tibial plateau width and lateral tibial plateau width were .99 cm and 1.19 cm respectively. Discussion/Conclusion: ACL primary and secondary injury occur at very high rates in the skeletally immature, especially in females at age 11 and older, and in males at age 13 and older. This data set offers some preliminary values for posterior tibial slope in patients without a history of ACL injury, allowing for comparisons to patients with ACL Injury. Increased tibial slope is a risk factor for ACL injury. In the skeletally immature, one option to alter the tibial slope is the use of guided growth with implants to slow the anterior growth of the proximal tibia, reducing the posterior slope of the tibia, and possibly lower the risk of ACL injury in this high-risk population. Fig 1. The mid region of the medial femoral condyle in relation to the medial tibial plateau. Posterior tibial slope angle measurements were taken at this coronal view slice position. Fig 2. The posterior tibial slope angle measurement of the medial tibial plateau in reference to the diaphysis of the tibia. Fig 3. The width of the anterior medial and lateral tibia plateau. Fig 4. The medial tibial plateau posterior slope plotted against age. Fig 5. The lateral tibial plateau posterior slope plotted against age. Table 1. The mean posterior tibial slope angles according to age and number of specimens. Age Number of Specimens Mean Media Posterior Tibial Slope Angle Mean Lateral Media Posterior Tibial Slope Angle 2 3 7.56˚ 12.15˚ 4 5 8.34˚ 4.96˚ 5 5 4.00˚ 3.08˚ 7 7 4.80˚ 3.87˚ 9 10 6.78˚ 6.73˚ 10 2 3.85˚ 6.17˚ 11 6 4.07˚ 5.10˚ 12 1 6.36˚ 11.84˚ All Specimens 39 5.53˚ 5.95˚ Table 2. The mean anterior medial tibial plateau width and lateral tibial plateau width according to age. Age Number of Specimens Medial Tibial Plateau Thickness (cm) Lateral Tibial Plateau Thickness(cm) 2 3 0.68 0.74 4 5 0.92 0.90 5 5 0.87 0.96 7 7 0.96 1.04 9 10 1.14 1.29 10 2 1.29 1.41 11 6 1.07 1.54 12 1 1.05 1.63 All Specimens 39 0.99 1.19